Multicenter Evaluation of the Candida albicans/Candida glabrata Peptide Nucleic Acid Fluorescent In Situ Hybridization Method for Simultaneous Dual-Color Identification of C. albicans and C. glabrata Directly from Blood Culture Bottles - Shepard, Janeen R. (American Society for Microbiology (ASM), 2008)
We evaluated the performance of the Candida albicans/Candida glabrata peptide nucleic acid fluorescent in situ hybridization (PNA FISH) method, a rapid two-color assay for detection of C. albicans and C. glabrata, in a multicenter study. The assay is designed for use directly from positive blood culture bottles in a FISH format. Intact, fixed cells are labeled fluorescent green (C. albicans) or fluorescent red (C. glabrata) by rRNA hybridization of fluorophore-labeled PNA probes. Results are available <3 h after cultures signal positive. An evaluation of 197 routine blood culture bottles newly positive for yeast by Gram staining was performed at five hospitals. The sensitivities of detection for C. albicans, and C. glabrata were 98.7% (78/79) and 100% (37/37), respectively, and the specificity for both components of the assay was 100% (82/82). The assay was also evaluated with 70 fungal reference strains and was challenged in the BacT/ALERT microbiological detection system with spiked blood culture bottles. These results support the use of the assay for rapid, simultaneous identification of C. albicans and C. glabrata in positive blood culture bottles. This rapid assay may aid in the selection of initial antifungal drugs, leading to improved patient outcomes.